STAR hovering test - Proof of functionality and representative results - - Hoffmann, F.; Schneider, O.; Wall, B.G. van der; Keimer, R.; Kalow, S.; Bauknecht, A.; Ewers, B.; Pengel, K.; Feenstra, G. (My University, 2014)
Within the DLR project AcTOR (Active Twist Optimized Rotor), a four-bladed, fully instrumented active twist model rotor was built. This active twist rotor was supposed to be tested in the LLF (Low Speed Facility) of DNW within the framework of the international STAR (Smart-Twisting Active Rotor) consortium. The STAR consortium is composed of ONERA, NASA, US Army AFDD, JAXA, Konkuk University, and KARI. In preparation to the planned DNW wind tunnel tests, a comprehensive preparatory test was conducted at the rotor preparation hall of DLR. The aim of this test had been the proof of functionality for the complete wind tunnel model with emphasis on active twist and blade performance. Besides basic rotor data, also advanced data concerning blade deformation and vortex properties for hover applications with and without active twist were aquired. Although, the functionality of the active twist blades and the rotor test stand could be demonstrated successfully, endurance problems occured during the test and hindered the project from a wind tunnel entry. Nevertheless, a comprehensive data base on an active twist model rotor in hover has been gained. The paper provides an overview of the preparatory test and presents representative results.